Development And Evaluation Of Taste Masked Orally Disintegrating Tablets Of A Water Soluble Drug, Sumatriptan Succinate And A Water Insoluble Drug, Ondansetron - Ravi, Sheshala (2010)

(untitled)
The aim of the present research was to formulate taste masked orally disintegrating tablets (ODTs) of ondansetron (water insoluble) and sumatriptan succinate (water soluble) using different available technologies namely Orasolv, freeze drying and Wowtab. In Wowtab and freeze drying techniques, the bitter taste of ondansetron was masked by the addition of a sweetener (aspartame), whereas in the Orasolv technique by complexing the drug with Eudragit EPO (1:0.5). In all the techniques used to prepare sumatriptan succinate ODTs, the intensely bitter taste of the drug was masked by coating it with Eudragit EPO (1:1) using spray dryer.